Discursive Creation Technique of English to Indonesian Subtitle in Harry Potter: The Chamber of Secrets Movie - Istiqomah, Lilik; Erawati, Medy; Suparno, Sonya Lianti (Lingual Journal of Language and Culture, 2019)
The purpose of this paper is to analyze the used of discursive creation technique of English to Indonesian subtitle in Harry Potter: The Chamber of Secrets movie. This research is descriptive qualitative method. Data of this research are utterances or sentences in subtitle movie of bilingual edition, both English and Indonesian. While, the source of data of this research is Harry Potter: The Chamber of Secrets movie. The researchers only used one data source, it was document. In analyzing the data, the researchers used comparison method to compare between the SL and TL that were analyzed. The result of this research shows that discursive analysis divided into three catogories of language unit, they are word 23%, phrase 20%, and sentence 57%. Therefore, it can be concluded that the translator has many errors in the sentence translated because he choose the easy sentence in order to make viewer understand the subtitle.